WEAK LISTENING SKILLS AND EFFECTIVE WAYS OF IMPROVING LISTENING COMPETENCE - Alimova Dildora Komiljon kizi; Zokirova Ziyodaxon Murod kizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
In the modern globalized world, learning foreign languages has become increasingly important, and listening skills are considered one of the most essential yet challenging components of language acquisition. Many learners, despite having strong grammar knowledge and a wide vocabulary, face significant difficulties in understanding spoken language in real-life situations. Factors such as fast speech, different accents, connected speech, and pronunciation variations make listening comprehension even more complex. This article examines the main causes of weak listening skills in detail. Particular attention is given to cognitive load, psychological barriers such as anxiety and lack of confidence, insufficient exposure to authentic listening materials, and poor phonetic awareness. Furthermore, the article provides practical and effective strategies for improving listening competence. These include regular exposure to audio input, the use of authentic materials such as podcasts and movies, the shadowing technique, focusing on general meaning rather than individual words, and step-by-step progression in difficulty levels. The findings of the study indicate that with consistent practice and the use of appropriate strategies, learners can significantly enhance their listening comprehension and overall communicative competence.